Effects of exercise training on blood lipids and lipoproteins in children and adolescents - Stoedefalke, K. (Journal of Sports Science & Medicine, 2007)
The following review aims to describe what is known about the effects of exercise training in children and adolescents on the following blood lipids and lipoproteins: total cholesterol (TC), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), and triglycerides (TG). Only studies that described mode, frequency, duration and intensity of the exercise were included in the review. The results of the studies reviewed were equivocal. Clearly the effects of exercise training on the blood lipid and lipoprotein levels of normolipidemic children and adolescents are equivocal. Of the 14 studies reviewed, six observed a positive alteration in the blood lipid and lipoprotein profile, four of the studies observed no alteration in the blood lipid and lipoprotein profile and one study observed a negative effect on HDL-C but an overall improvement in the lipid and lipoprotein profile due to the decrease in the TC/HDL ratio. It appears that methodological problems present in the majority of the exercise training studies limits the ability to make a conclusive, evidence based statement regarding the effect exercise training has on blood lipid levels in normolipidemic children. Most of the research design flaws can be linked to one or more of the following: small numbers of subjects in each study, low or no representation of girls, inclusion of both boys and girls in the subject pool, inclusion of boys and girls at different maturational stages in the subject pool, exercise training regimes that do not adequately control for exercise intensity, exercise training regimes that do not last longer than 8 weeks and exercise training studies that do not have an adequate exercise volume to elicit a change. Ideally, future research should focus on longitudinal studies which examine the effects of exercise training from the primary school years through adulthood.